The Personality Structure of the Main Character in Marwah Mamduh’s Novel Na’am Ahwâkarya - Puja Rahmah; Syarifuddin Syarifuddin (Buletin Al-Turas, 2021)
This study aimed to describe the personality structure of the main character in Marwah Mamdouh’s novel Na'am Ahwaka using Sigmund Freud's psychoanalytic approach. Marwah Mamdouh presented a fictional story that illustrated the personality structure form, namely the condition of the soul and the emotional outbursts experienced by the character. This research employed a qualitative descriptive method to express the personality structure forms of the main characters in the novel. The obtained research data as words, phrases, sentences, and discourse showed the personality structure of the main characters in the novel. The findings of the research were narratives that showed the structure of personality comprising, first, Id which was a part of the psychology; second, Ego which was the only area of the mind that had contact with the reality; third, Super Ego was the absorption of individuals from combined values and moral values that provide a boundary between the good and bad things. This study concluded that id dominated all the problems experienced by the main character in the novel.